2018
DOI: 10.1590/0034-737x201865060001
|View full text |Cite
|
Sign up to set email alerts
|

Relações entre parte aérea e raízes em povoamentos de teca

Abstract: RESUMO Há pouca informação disponível sobre a relação entre folhas e raízes de teca, cultivada no Brasil. O objetivo deste trabalho foi avaliar se a biomassa dos componentes da parte aérea e a área foliar são bons estimadores da biomassa e da superfície de raízes, em povoamentos de teca (Tectona grandis). Na amostragem, realizada em árvores de teca, com 17 e 90 meses de idade, em parcelas estabelecidas em talhões comerciais em Tangará da Serra, MT, foram individualizados os componentes raízes, folhas, galhos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…When the above-ground carbon stock was determined in a Brazilian teak stand at different ages, Almeida et al ( 2010) obtained mean values of 5.62 t of C per ha -1 at 2.5 years and 14.15 t of C per ha -1 at 3.5 years, which is similar to those estimated in the present study. However, below-ground stock results were higher, with 6.7 t of C per ha -1 at 2.5 years and 4.9 t of C per ha -1 at 3.5 years, due to the differences in the soil chemical elements available for teak roots' development (Behling et al 2018).…”
Section: Resultsmentioning
confidence: 90%
“…When the above-ground carbon stock was determined in a Brazilian teak stand at different ages, Almeida et al ( 2010) obtained mean values of 5.62 t of C per ha -1 at 2.5 years and 14.15 t of C per ha -1 at 3.5 years, which is similar to those estimated in the present study. However, below-ground stock results were higher, with 6.7 t of C per ha -1 at 2.5 years and 4.9 t of C per ha -1 at 3.5 years, due to the differences in the soil chemical elements available for teak roots' development (Behling et al 2018).…”
Section: Resultsmentioning
confidence: 90%
“…Among the vermicompost substrates, the substrate V4 had the worst performance, differing statistically from the substrates V1 and V2, these being the treatments with greater root growth and more branched roots. Behling et al (2018), studying the relationship between shoot and roots in teak plants, concluded that there are significant, linear and potential relations between the aerial part and the roots of the species, and that leaf area (LA) is a good estimator of the root surface area of teak plants, with the photosynthetic rate per unit of leaf area modulated by the root system. The results of this study indicate the same pattern for P. dubium plants, with higher results of LA in vermicompost substrates than the commercial substrate (control).…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study suggest that melatonin was correlated with higher shoot dry matter weight, indicating that it stimulates greater allocation of dry matter to shoots than to roots, which is also shown by the lower RS. According to Behling et al 30 , the relationship between leaf dry matter and root dry matter reflects an approximate source and sink relationship. At 69 DAP, the M43 treatment provided a larger source area, which may be reflected in a higher CO 2 content being fixed and redistributed throughout the plant.…”
Section: Discussionmentioning
confidence: 99%